Strategi Seksi Penyelenggaraan Umroh Dalam Mengawasi Travel Yang Bermasalah Di Kementerian Agama Kota Palembang - Dea Anggraini; Candra Darmawan (Social Science and Contemporary Issues Journal, 2024)
This thesis is entitled "supervisory strategy for Umrah organizers in monitoring problematic travel in Palembang City". The aim of this research is to find out how the Ministry of Religion of Palembang City monitors travel in Palembang City. This type of research is field research, namely research that collects data in the field, located at the Ministry of Religion, Palembang City. This data collection technique is descriptive qualitative through three stages, namely data reduction, data presentation, and drawing conclusions. This researcher uses supervision theory by Soadang P. Siagan. Supervision at the Ministry of Religion of Palembang City using an internal control system shows that the strategy of the Office of the Ministry of Religion of Palembang City in implementing its supervision is in an orderly, disciplined manner and following the rules, by controlling the level of travel compliance through the monitoring application/web which is carried out online by utilizing PUSAKA (Service Center). Religious). To improve this monitoring function for travel in Palembang City, it is best to carry out routine monitoring. The supervision process at the Ministry of Religion uses direct and indirect supervision. The implementation of the monitoring process carried out by the Ministry of Religion regarding travel is not yet optimally carried out directly, but the Ministry of Religion also carries out supervision via online/web. Because there is no set time to carry out direct supervision after the departure of the congregation. However, this is still effective for the Umrah travel party, therefore the Umrah travel party can trust the pilgrims.Keywords: Ministry of Religion supervision, Umrah Travel